If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -7 = 7 Reorder the terms: -7 + 3z = 7 Solving -7 + 3z = 7 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3z = 7 + 7 Combine like terms: -7 + 7 = 0 0 + 3z = 7 + 7 3z = 7 + 7 Combine like terms: 7 + 7 = 14 3z = 14 Divide each side by '3'. z = 4.666666667 Simplifying z = 4.666666667
| -2p-5(3-2p)=6(p-4)-3 | | x/8-5=8 | | 4a+5b=47 | | x^2(x+10)=39 | | 4-n/3= | | 9x-(7x+9)=3x-29 | | (21+17)+x=21+(17+5) | | 7/9y-4=17 | | tan^3(x)-sec(x)=-1 | | -y+4(2y-3)=5y-6(y-7) | | -3/7x=18 | | 129+48x=201 | | X/6-3=2 | | 7*x^2-14=0 | | 129+48x=2-1 | | (3x+5)+(4x-6)=180 | | 3[z-(5z+17)+5]=5(z+3) | | 4(u-3)-8u=28 | | 8+2n=4n+6 | | 6t-5=13 | | -6+14x=50 | | -6+14x=56 | | 6x^1/4-x^1/2=9 | | -6+14=56 | | -7v+4(v+4)=-14 | | 2x^2-2x+1=18 | | 2(x+8)=4x+7 | | 10x-14=9x+10 | | 124-86=36 | | 3/7=2/3y | | 6m+8=10 | | -logx=0 |